(untitled) (KULT_online, 2016)
Lars Wilhelmer’s monograph Transit-Orte in der Literatur. Eisenbahn – Hotel –Hafen – Flughafen deals with the literary conception of modern and late-modern age places of transition as resemblances of Augé’s concept of “non-places.” After a short theoretical introduction to spatial theory, Wilhelmer provides a diachronic account of German literary examples, such as Transit by Anna Seghers. These works are used to exemplify the function of different places of modern and post-modern transition as spatial element and are put into their historical context. Thus an analytical approach in the sense of transitional spatial theory is used, exemplified, and displays the theoretical fundament given by the first part of the book.